1999
DOI: 10.1016/s0378-1135(99)00013-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of eae+ Escherichia coli isolated from healthy and diarrheic calves

Abstract: Strains of Escherichia coli from 101 healthy and 114 diarrheic calves were screened by PCR for the eae (intimin) gene and Shiga toxin genes (stx). Each eae+ and eae/stx+ strain was examined for antimicrobial susceptibility, enterohemolysin activity, and the somatic O antigen was determined. An immunoassay was used to detect Shiga toxin antigens for the eae/stx+ E. coli. Significantly more (p = 0.005) of the healthy calves carried eae+ and eae/stx+ E. coli in their feces when compared to strains from diarrheic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
7
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 51 publications
5
40
7
1
Order By: Relevance
“…Cephalothin and tetracycline showed the highest rates of resistance, 46.1% and 45.7% respectively (Table 2). Thirty-four percent of the isolates showed resistance to 8-10 antimicrobial agents; a rather high rate that agrees with the results reported by Lazaro et al (1994) among diarrheic calves in Rio de Janeiro, Brazil They found 80.0% of the isolates showing multidrug resistance. Indirect selection for multiresistant strains will contribute to the increase of emerging antimicrobialresistant pathogens, and facilitate the spread of these mobile resistance elements to other bacteria.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Cephalothin and tetracycline showed the highest rates of resistance, 46.1% and 45.7% respectively (Table 2). Thirty-four percent of the isolates showed resistance to 8-10 antimicrobial agents; a rather high rate that agrees with the results reported by Lazaro et al (1994) among diarrheic calves in Rio de Janeiro, Brazil They found 80.0% of the isolates showing multidrug resistance. Indirect selection for multiresistant strains will contribute to the increase of emerging antimicrobialresistant pathogens, and facilitate the spread of these mobile resistance elements to other bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…Among the 173 E. coli isolates studied from northwestern of São Paulo State, 85 (49.1%) were found to be positive for at least one of the virulence factors examined, a result similar to that reported by Salvadori et al (2003). A wide range of serogroups in cattle has already been reported (Holland et al, 1999;Wani et al, 2003), some only in bovines, and others, like O26, O103, O111 and O157 both in bovines and humans (Paton and Paton, 1998). Saridakis et al (1997) reported the isolation of E. coli serogroups O26, O114, O119, O125, O128, O142 and O158 from diarrheic calves in Brazil, in agreement with the results reported here.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, Shiga toxins seem to play a major role in the pathogenesis of haemorrhagic colitis and haemolytic-uremic syndrome by inducing microvascular changes in vivo and are cytotoxic to selected cell lines in vitro. Intimin facilitates the adherence to intestinal villi producing attaching and effacing lesions, and although the role of enterohaemolysin in an intestinal disease is unclear, it has been suggested that enterohaemolysins may enhance the effects of Shiga toxins (Holland et al, 1999;Caprioli et al, 2005). Sporadic cases or large STEC outbreaks in humans are associated with the consumption of raw or undercooked meat of food animals and other foods contaminated by animal faeces, and also by contact with STEC-positive animals or with their environment (Paton and Paton, 1998b).…”
mentioning
confidence: 99%
“…The pathogenicity of these bacteria is associated with virulence genes encoded by plasmids, bacteriophages, or pathogenicity islands (PAI). These genes include the plasmid-encoded genes for enterotoxins and fimbriae or pili, the phage-encoded genes for Shiga toxins (Stx 1, 2), and the PAI-encoded genes for the attaching and effacing (AE) lesion in enteropathogenic E. coli (EPEC) and enterohaemorrhagic E. coli (EHEC), as well as the pap, hly, and cnf1 genes in uropathogenic E. coli (UPEC) (10,14,21).…”
Section: Praca Oryginalnamentioning
confidence: 99%